2019
DOI: 10.1002/fsn3.1311
|View full text |Cite
|
Sign up to set email alerts
|

Changes of bioactive compounds in barley industry by‐products during submerged and solid state fermentation with antimicrobial Pediococcus acidilactici strain LUHS29

Abstract: In this study, changes of bioactive compounds (crude protein (CP), crude fat (CF), dietary fiber (DF), fatty acids (FAs), free amino acids (FAAs), phenolic compounds (PCs), biogenic amines (BAs), lignans, and alkylresorcinols) in barley industry by-products (BB) during submerged and solid state fermentation (SSF) with Pediococcus acidilactici were analyzed. It was established that both fermentation conditions reduce the CP and CF content in BB (by 25.8% and 35.9%, respectively) and increase DF content (on aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The previous research of Bartkiene et al. (2020) showed that the total BA content in barley by‐products was reduced after SSF and SMF with P. acidilactici LUHS29. It was reported that L. plantarum , L. sakei , L. pentosus , Pediococcus acidilactici, and L. casei had the ability to degrade in vitro tyramine histamine and putrescine (Alvarez & Moreno‐Arribas, 2014).…”
Section: Resultsmentioning
confidence: 87%
“…The previous research of Bartkiene et al. (2020) showed that the total BA content in barley by‐products was reduced after SSF and SMF with P. acidilactici LUHS29. It was reported that L. plantarum , L. sakei , L. pentosus , Pediococcus acidilactici, and L. casei had the ability to degrade in vitro tyramine histamine and putrescine (Alvarez & Moreno‐Arribas, 2014).…”
Section: Resultsmentioning
confidence: 87%
“…Many factors influence the fermentation process (microorganisms, substrates, moisture content, environmental conditions, etc.). However, complex compounds are metabolized into simpler forms [23]. The types of microorganisms and their characteristics, as well as the fermentation conditions, will result in the formation of different final metabolites, such as lactic acid, bacteriocins, ethanol, etc., because different microorganisms may react distinctly to specific substrates and conditions [35].…”
Section: Fermented Feed Characteristicsmentioning
confidence: 99%
“…In this study, we hypothesized that antimicrobial property possessing LAB can contribute to safe local feed stock incorporation in piglets' diet, modify the microbiota of piglets, and ensure health and growth performance of the animal. Furthermore, fermented feed is already partly degraded, including degradation of protein to free amino acids [22][23][24]. Therefore, we also hypothesized that fermented feed will reduce ammonia emission.…”
Section: Introductionmentioning
confidence: 99%
“…The L. plantarum LUHS122, L. casei LUHS210, L. farraginis LUHS206, P. acidilactici LUHS29, L. plantarum LUHS135 and L. uvarum LUHS245 strains were obtained from the Lithuanian University of Health Sciences collection (Kaunas, Lithuania). Our previous studies showed that the above-mentioned strains inhibit various pathogenic and opportunistic microorganisms and are suitable for fermentation of various cereal substrates [18][19][20][21][22], as well for rapeseed meal fermentation [23]. The rapeseed meal, water and LAB strains (equal parts of each strain by volume) suspension (3% from dry matter of feed mass, v/m), containing 8.9 log 10 colony forming units CFU/mL, was fermented at 30 ± 2 • C for 12 h. The fermentation process involves wheat and rapeseed meal (1:1 ratio).…”
Section: Lab Strains Used For Feed Fermentation Feed Fermentation Anmentioning
confidence: 99%